Study on Spatial Differentiation Characteristics and Driving Mechanism of Sustainable Utilization of Cultivated Land in Tarim River Basin - Yang Sheng; Weizhong Liu; Hailiang Xu (Land)
The sustainable utilization of cultivated land is a crucial prerequisite for ensuring food security and achieving sustainable socioeconomic development. This study employed a dataset to evaluate sustainable land use and utilized a combination of multi-factor comprehensive evaluation models, structural equation modeling, geographically weighted regression, and Pearson correlation analysis to systematically investigate the overall level, spatial differentiation characteristics, and driving mechanisms of sustainable cultivated land utilization in the Tarim River Basin. Additionally, we compared and tested three spatial interpolation methods using high-resolution data to address the modifiable areal unit problem (MAUP) and enhance the quality of spatial predictions for cultivated land utilization, ultimately identifying inverse distance weighting (IDW) as the optimal method. The results indicate the following: (1) The level of sustainable cultivated land utilization is moderately high, with an average index of 0.581, exhibiting a “U-shaped” trend from the upper to lower reaches of the Tarim River Basin. The highest levels are found in the Kashgar River–Yarkant River Basin, followed by the Hotan River Basin and the Kaidu–Peacock River Basin, while the mainstream area has the lowest levels. (2) The relationships among various cultivated land environmental systems and sustainability demonstrate distinct response characteristics and spatial differentiation patterns. Cultivated land use and management exert the most significant influence on sustainability, followed by soil quality and water resource systems, with climatic factors having the least impact. The effects of each system reveal inverted “U”, inverted “N”, “U”, and “W” patterns from the lower reaches to the upper reaches, respectively. (3) As the complexity of interactions and integrative mechanisms within the regional cultivated land system increases, the sensitivity and vulnerability of the system also rise, resulting in lower levels of sustainable utilization. (4) Based on the current challenges facing the cultivated land environmental system and the primary mechanisms influencing its sustainability, we propose regulatory measures focused on “suitable consolidation”, “suitable resting”, and “suitable planting”. These findings provide valuable insights for formulating differentiated land protection strategies, policies, and spatial planning initiatives.